2003
DOI: 10.1046/j.1440-1746.2003.03179.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of increased insulin resistance in non‐cirrhotic patients with chronic hepatitis C virus infection

Abstract: Collectively, hepatic fibrosis and inflammation appear to play key roles in the increase in insulin resistance in patients with chronic HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 32 publications
3
54
1
1
Order By: Relevance
“…Rather, IR in CHC seems to be due to direct virus-specific effects on insulin signaling. Thus, initial studies noted increased serum levels of TNF-α in subjects with CHC [66][67][68] or showed a correlation with IR [69] but did not adequately correct for potential confounders. A later well-controlled study compared 154 HCV-infected non-diabetic males with 75 matched uninfected controls [65] .…”
Section: Inflammation and Irmentioning
confidence: 99%
“…Rather, IR in CHC seems to be due to direct virus-specific effects on insulin signaling. Thus, initial studies noted increased serum levels of TNF-α in subjects with CHC [66][67][68] or showed a correlation with IR [69] but did not adequately correct for potential confounders. A later well-controlled study compared 154 HCV-infected non-diabetic males with 75 matched uninfected controls [65] .…”
Section: Inflammation and Irmentioning
confidence: 99%
“…However, other studies have suggested that HCV may be directly involved in the development of type 2 DM or insulin resistance even in those without cirrhosis [8,[17][18][19] 491 HCV-infected persons over the age of 40 years in a nationwide cross-sectional study [11] and then in a longitudinal cohort study found that those with HCV infection were at increased risk for developing DM with increasing age and body mass index (BMI). Another nationwide crosssectional study dividing patients into young and old groups found an association of HCV and DM in those who were younger and had a family history of DM [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports state that diabetes is associated with persistent HCV infection (22,23). Because she had received highdose corticosteroid therapies, we are not certain about the cause-effect relationship, but the possibility remains.…”
Section: Discussionmentioning
confidence: 99%